مدخل التحسين المستمر Kaizen وأثره على أداء المنظمات بالتطبيق على الشركة القابضة لكهرباء مصر - بكر، نادية عبدالخالق رمضان (المنظمة العربية للتنمية الإدارية, 2016)
يسعى هذا البحث لتحديد الإطار النظري والفلسفي لمنهجية كايزن (Kaizen) في الإدارة، أو التحسين المستمر للأداء، ودراسة اتجاهات القيادات الإدارية في القطاع محل الدراسة نحو تلك المنهجية من حيث مدى الإلمام بالمفاهيم الأساسية حولها، وأهم المهارات الإدارية والعناصر اللازمة لتطبيقها، وأهم الآثار والنتائج المترتبة على تطبيقها، ومن ثم إمكانية تقديم مجموعة توصيات وآليات تنفيذها لتحقيق فعالية تلك المنهجية في القطاع محل الدراسة، والنهوض بمستوى الأداء به. ولتحقيق أهداف البحث واختبار فروض الدراسة تم استخدام المنهج الوصفي التحليلي، ومن أهم النتائج التي توصلت إليها الباحثة أن هناك انخفاض كبير في مستوى المديرين في القطاع محل الدراسة، فيما يتعلق بفعاليتهم في تحقيق تلك المنهجية، ويرجع ذلك إلى عدم الإلمام بالمفاهيم الأساسية لمنهجية الإدارة بالكايزن، والمهارات والعناصر اللازمة لتحقيقها، ومن ثم وجدت أن هناك انخفاض كبير أيضا في النتائج المترتبة على ذلك والمتعلقة بمستوى الأداء التنظيمي من حيث نشر روح التعاون، والعمل بروح الفريق، وتحقيق الإبداع والتغيير التنظيمي المستمر، وتحقيق التعلم التنظيمي، وتحقيق الارتباط والولاء التنظيمي للعاملين، وتحسين جودة الخدمة وسرعة الأداء، ورضا العملاء به.
This research seeks to determine the theoretical and philosophical framework for the systematic administration kaizen or continuous improvement of performance according to the literature of Behavioral Sciences. The Study also seeks to analyze administrative leadership trends in the sector under study about the methodology in terms of the extent of knowledge of the basic concepts, and the most important managerial skills and the elements necessary for the application, moreover the study seeks to analyze the most important effects and consequences of the application, finally the study ends up with set of recommendations and mechanisms to be implemented in order to achieve the effectiveness of the methodology in the sector specified and consequently an advancement of the level of its performance To achieve the objectives of research and testing hypotheses, the researcher uses descriptive analytical method, in addition to the empirical study approach. The most important results show that there was a significant decrease in the level of managers in the sector under consideration with respect to effectiveness in achieving those methodologies due to a lack of knowledge of kaizen concepts, and skills and the elements necessary to achieve them. Results also indicat that there was a significant decline on the level of organizational performance in terms of the deployment of the spirit of cooperation teamwork, creativity and constant organizational change, and the achievement of organizational learning. There was also declining awareness of the link between organizational loyalty, and improved quality of service, pace of performance, and customer satisfaction in sector under study
Keywords: الفكر الإداري -- منهجية كايزن -- التحسين المستمر -- القيادات الإدارية -- التنمية المهنية